Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Dan Kepemilikan Saham Terhadap CSR - Devito Gandawidjaya, Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to determine the relationship of company size, profitability,leverage and public share ownership on CSR. The purpose of analyzing the direction and influence of company size, profitability, leverage and public share ownership on CSR. This study uses manufacturing companies listed on the Indonesia Stock Exchange during 2016-2018 as a population. The sample selection uses a purposive sampling technique from a total of 47 companies that have passed the research criteria. The results of this study indicate that company size has a significant positive effect on CSR, profitability has a significant positive effect on CSR, leverage has a significant negative effect on CSR and public share ownership has a significant positive effect on CSR in manufacturing companies.